RECENT HR PRACTICES: A TRANSITION TOWARDS ORGANISATIONAL TRANSFORMATION - Kumar, Ajit (International Journal of Research -GRANTHAALAYAH, 2016)
Today the world of work is rapidly shifting. Human Resource Management (HRM), as a part of organization, must be prepared to deal with effects of varying world of work. Thus, for the HR people it is all about comprehending the ramification of globalization, corporate downsizing, changing skill requirements, the contingent work force, work-force diversity, continuous improvement initiatives, decentralized work sites, re-engineering and employee involvement. Companies today are having a global mix of the employees which requires understanding of the employees and their mindset as it is a tough task for HRD. Human Resource Management is a course of bringing people & organization together, so that the objectives of each other are met. The organizations in Indian are witnessing a change in systems, management cultures and philosophy due to the global alliance of Indian Organization. As globalization has been a challenging concern for the organization because IHRM (International Human Resource Management) has placed significant stress on number of functions & responsibilities, such as orientation, relocation, translation services to help employees adapt to new and different milieu outside their own country. Hence forth, the essential attention must be taken by HR Managers in devising procedures, maintaining the relationship, policies, motivational strategies, and stressing on value in administration. HR people need to do a lot of things in this regard. At the end HRD plays a vital role as a planner, initiator and executor in every organization. The paper thus discusses few emerging concepts, trends and practices of the HRM like tapping skills anytime & anywhere, managing people as a workforce of one, the rise of the extended workforce, HR driving the agile organization, reconfiguring the global talent landscape, workforce on demand, HR and people analytics, data driven and social media recruiting, HR technology solutions as enabler etc. The paper highlights on few of the most key HR initiatives and trends which the HRM function has to take care so as to make an organisation sustainable and gain success.